Antifungal activity of Allamanda spp. extracts and their microemulsion formulations against anthracnose (Colletotrichum gloeosporioides) disease of papaya - Haron, Farah Farhanah (2012)
An effective and efficient microemulsion biofungicide derived from Allamanda spp. was developed for the control of Colletotrichum gloeosporioides, the most important pathogen of papaya anthracnose. Leaf extracts of Allamanda blanchetti, Allamanda cathartica, Allamanda cathartica ‘Alba’, Allamanda cathartica ‘Jamaican Sunset’ and Allamanda oenotheraefolia were screened for antifungal activities in vitro and extracts that showed strongest activity were screened in vivo. Petroleum ether,chloroform and methanol extracts of all species resulted in production of antifungal substances that significantly inhibited the growth of C. gloeosporioides (P<0.05). Antifungal activity of chloroform extract of A. cathartica ‘Alba’, A. cathartica ‘Jamaican Sunset’ and A. blanchetti gave the smallest mean of percentage inhibition of radial growth (PIRG) and number of spores as compared to A. cathartica and A.oenotheraefolia where maximum inhibition (100%) was observed with the 5 mg/ml and higher treatments. SEM observations showed that active crude extracts resulted in hyphal degradation which the hyphae were retarded and agglutinated. Results proved that Allamanda spp. possessed fungistatic and fungicidal properties and the effect increased at higher extract concentrations. A significantly lower disease incidence, severity, and index were observed in Allamanda treated papaya fruits. Fruits coated with chloroform extract of A. cathartica ‘Jamaican Sunset’ at 5 and 7 mg/ml concentrations showed maximum reduction in anthracnose incidence (17% and 0%, respectively) and disease severity scores were always 1 (1-25%) and 0 (0%). Antifungal effects of the most effective extracts of all Allamanda spp. were supported by the presence of chemical constituents identified by GC-MS. Campesterol, -sitosterol, stigmasterol, plumericin, squalene, and α-Tocopherol were detected as major compounds in Allamanda species that were possibly responsible for the antifungal activity. Bioautography-guided isolation was performed on the chloroform extract of A. cathartica ‘Jamaican Sunset’ and based on the available spectral data from MS, IR, 1H-, 13C-, DEPT-135, HMQC, HMBC, COSY NMR spectra obtained on a Varian AS 400 spectrometers using CDCl3 as solvent, the pure active antifungal sesquiterpene was identified as plumericin (C15H14O6, MW: 290). Microemulsion formulation was prepared by constructing ternary phase diagrams between alkyl polyglucosides (APG) surfactants (Agnique MBL 510 H or/and Agnique MBL 530 H), dimethylamide carrier oil (Agnique AMD 810), and water, in order to select the best points from the isotropic microemulsion regions. From the seven phase diagrams constructed, eight microemulsion solutions were derived and all solutions were stable after 4 weeks. Surface tension values of microemulsion solutions were in the range of 29 to 31 mN/m, while particle sizes were in the range of 51.79 to 1801.05 nm. Allamanda microemulsion was formulated with the active ingredient (a.i), Allamanda concentrated liquid crude extract (ACLCE) with 9.75% plumericin. The formulations were evaluated for their efficacy in controlling papaya anthracnose and their effects on the postharvest quality of treated fruits during storage. Overall,the eight formulations showed very good activity in reducing the incidence and index of anthracnose to as low as 0 to 28% at concentration of 7% w/w while severity scores were always 0 and 1 (0-25%), in comparison with Benocide®. Allamanda microemulsion coatings delayed ripening process (10 ºC, 80% RH) in commercial packaging observed by the minimum weight loss, slower change in external peel colour, greater firmness which were good in maintaining the storage quality of papaya up to 30 days without affecting their soluble solids concentration (SSC) values as compared to control. A fungicide composition of nano-emulsified homogeneous mixture coded as AM8,comprising 35% w/w of Allamanda concentrated liquid crude extract (ACLCE), 26% w/w aqueous medium (water), 13% w/w of alkylpolyglucoside surfactant and an oil phase of dimethylamide of 26% w/w (AM8), was chosen as the best Allamanda microemulsion formulation (Patent No.: PI2011004439). It was designed and optimized to achieve maximum fungicide performance with EC50 and EC95 values of 7.067 and 18.390% (w/w) at 95% confidence limit, had a shelf life up to six months,and was found to be more effective and efficient in comparison with the common commercial fungicide formulation, Benocide® (benomyl 50% WP).